RAILWAY CROSSINGS AS A CRITICAL POINT S OF CONFLICT SITUATIONS (Perner's Contacts, 2018)
In the Czech Republic is relatively dense road and rail network. In many places, therefore, leads to a crossing of these transport routes. Level crossing of rail track with roads (level crossing) carry with them the possibility of emergence of conflict situations, which prevent traffic accidents. Traffic accidents are one of the indicators of the safety of road and rail transport. In the article are processed by the selected statistical data relating to the system of road and rail transport, railway crossings and traffic accidents on them.
Keywords: railway crossing, a traffic accident at a railway crossing, evaluation of accident rate.